PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM (Media Riset Akuntansi, 2022)
exchange, especially the mining sector. This study also aims to determine the effect of return on equity, earnings per share and debt to equity ratio of stock prices in mining companies listed on the Indonesia Stock Exchange period 2012-2015. The research method used in this research is descriptive analysis. Sources of data used in this study is the publication data of annual financial reports of mining industry companies    listed    on    the    stock    exchange     Indonesia.Based on the test results found ROE and EPS value significantly influence on stock prices which means a direct relationship with the stock price of mining sector companies.While for the test results DER value found no significant effect on stock prices which means the relationship is not in line with the stock price of mining sector companies.